Interferons and its use in children with COVID-19: A narrative review - Chairunnisa Chairunnisa; Suharjono Suharjono (Jurnal Ilmiah Farmasi, 2022)
Background: All ages, including children, are susceptible to the disease COVID-19. The severity of COVID-19 in children is mild than in adults. One of the recommended antiviral drugs for COVID-19 in children is interferon. Objective: To describe the efficacy and safety of using interferon in children with COVID-19 Method: The article is a narrative study. The main databases in the article search process in this literature review are PubMed and Google Scholar. Results: The articles could potentially be involved in this study were 28 articles. A total of 13 articles included the criteria, 9 articles discussed the use of interferon against respiratory syndrome, 4 articles on interferon in children, and one reference from a literature search. Conclusion: Interferon therapy in COVID-19 in children has a high cure rate but needs to be evaluated in a larger sample of pediatric patients.